Six weeks of static apnea training does not affect Hbmass and exercise performance - Bouten, J.; Debusschere, J.; Lootens, L.; Declercq, L.; Van Eenoo, P.; Boone, J.; Bourgois, J. G. (Journal of Applied Physiology, 2022)
Acute apnea is known to induce decreases in oxyhemoglobin desaturation (SpO2) and increases in erythropoietin concentration ([EPO]). This study examined the potential of an apnea training program to induce erythropoiesis and increase hematological parameters and exercise performance. Twenty-two male subjects were randomly divided into an apnea and control group. The apnea group performed a 6-wk apnea training program consisting of a daily series of five maximal static apneas. Before and after training, subjects visited the lab on 3 test days to perform 1) a ramp incremental test measuring Vo2peak, 2) CO-rebreathing for Hbmass determination and a 3-km time trial, and 3) an apnea test protocol with continuous finger SpO2 registration. Venous blood samples were drawn before and 180 min after the apnea test for analysis of [EPO]. Minimal SpO2 reached during the apnea test protocol was 91 ± 7% pre and 82 ± 7% post apnea training. The apnea test protocol did not elicit an acute increase in [EPO] (P = 0.685) before nor after the training program. Consequently, resting [EPO] (P = 0.170), Hbmass (P = 0.134), Vo2peak (P = 0.796), and 3-km cycling time trial performance (P = 0.509) were not affected either. The apnea test and training protocol, consisting of five maximal static apneas, did not induce a sufficiently strong hypoxic stimulus to cause erythropoiesis and therefore did not result in an increase in resting [EPO], Hbmass, Vo2peak, or time trial performance. Longer and/or more intense training sessions inducing a stronger hypoxic stimulus are probably needed to obtain changes in hematological and exercise parameters.